The Effect of Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) Return on Assets (ROA) in PT. Bank Sulselbar - Vira Ayustina; Chalid Imran Musa; Nurman; Anwar; Ahmad Ali (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this research is totest and analyze the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) at PT. Sulselbar Bank. The techniques for collecting secondary data are obtained from the Financial Data at PT. Sulselbar Bank. The population is the financial statements at PT. Bank Sulselbar from August 2017 to December 2021, and the samples taken are monthly data for 4 (four) years and 5 (five) months. So, the amount of data obtained is 53. The results of the research have been tested on classic assumptions such as the assumption of normality, the assumption of multicollinearity and the assumption of heteroscedasticity. By applying multiple linear regression techniques in the process of analyzing the data. The results showed that partially Non Performing Loans (NPL) had a negative and insignificant effect on Return on Assets (ROA) and Loan To Deposit Ratio (LDR) had a positive and insignificant effect on Return on Assets (ROA). Simultaneously Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) have a positive effect